Spraying-free polyurethane self-skinning foam material and preparation method thereof

By adjusting the A and B components of the polyurethane self-skinned foam material, combining physical foaming agents and low surface energy particles, the environmental pollution and insufficient performance caused by spraying mold inner paint is solved, and a high-performance polyurethane self-skinned foam material without spraying is achieved.

CN119591823AActive Publication Date: 2025-03-11WANHUA CHEM BEIJING
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311159669.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-11
Publication Date
2025-03-11
Estimated Expiration
2043-09-11

AI Technical Summary

Technical Problem

The existing polyurethane self-skinned foam materials need to be sprayed with mold paint during the production process, resulting in environmental pollution, rising costs and workers' health problems. At the same time, the material appearance is poor after being sprayed, and the wear and light resistance is insufficient.

Method used

By adjusting the components of material A, increasing the amount of grafted polyether polyol, adding low-surface energy particles and anti-aging agents, and introducing appropriate amounts of polymerized and modified isocyanates into material B, using physical foaming agents, avoiding the use of strong initiation catalysts, in order to prepare spray-free polyurethane self-crusting foam materials.

Benefits of technology

It achieves good appearance, wear resistance and light resistance of polyurethane self-skinned foam without spraying mold inner paint, meets production process and conventional performance requirements, and reduces production links and environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The invention discloses a spraying-free polyurethane self-skinning foam material and a preparation method thereof. The polyurethane self-skinning foam material comprises a material A and a material B, and is prepared by adopting a closed mold pouring process. According to the invention, the surface defect-free requirement is met by adjusting the ratio of grafted polyether to trifunctional polyether in the material A and the specific color paste ratio, various light-resistant and aging-resistant requirements after paint spraying are met by adding an aging aid, the friction-resistant requirement is met by using a physical foaming agent and low-surface-energy particles, and a foam production process is matched, so that the wear-resistant performance of the paint is improved. The polyurethane foam produced under the condition of no paint spraying can meet various requirements which can only be met by original paint spraying foam, such as excellent appearance, comfortable hand feeling and good light resistance and friction resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polyurethane materials, and specifically relates to a spray-free in-mold paint polyurethane self-skinning foam material and a preparation method thereof, and especially relates to a spray-free polyurethane self-skinning foam material containing a specific grafted polyether component ratio and low surface energy particles and a preparation method thereof. Background Art

[0002] Polyurethane integral skin foam is widely loved by consumers and manufacturers because it can form the surface material and the foam core material at one time. Therefore, it is widely used in car steering wheels, engine hoods, bicycle saddles, shoes, sporting goods, home armrests and seats, etc. However, it is usually necessary to spray in-mold paint in the production process to cover up the color difference and pinholes on the surface of the polyurethane foam, avoid yellowing of the foam and affect the appearance of the foam product, and improve the surface gloss to beautify the appearance and improve the feel. In-mold paint is usually obtained by the reaction of polyester and aliphatic isocyanate. This material is wear-resistant and insensitive to light. Therefore, the polyurethane foam sprayed with in-mold paint also has good wear and light resistance.

[0003] However, the process of spraying in-mold paint has many disadvantages, mainly including pollution (including to the environment and the foam product itself), increased carbon emissions, impact on worker health, and increased production material and time costs. In terms of pollution, the paint mist formed by spraying paint contains a large amount of organic pollutants such as benzene, styrene, toluene, formaldehyde, acetaldehyde, etc., which will have a serious negative impact on the environment, worker health and the VOC performance of the foam. Therefore, in order to meet environmental protection requirements, factories need to spend a lot of money on waste gas treatment every year. Workers need to wear gas masks and masks to avoid inhaling pollutants, and the VOC test of the foam often fails the test. For the production of self-skinning foam, in-mold paint is expensive, spraying in-mold paint during production takes time, and there are often problems such as increased scrap rate due to improper painting operation by workers.

[0004] If the in-mold paint is not sprayed in the existing self-skinning foam production, the foam surface will be dull, with serious color difference, densely covered with pinholes of different sizes, and the appearance cannot meet the factory requirements; the self-skin formed by polyurethane full-water foaming is thin and cannot meet the wear resistance requirements; the isocyanate used in commonly used polyurethane products is aromatic isocyanate, which easily turns yellow when exposed to light and cannot meet the light resistance requirements, and the color changes significantly within a short time after leaving the factory.

[0005] Patent CN101597370B discloses a method for preparing a water-foamed self-skinning polyurethane composition, which obtains a self-skinning foam product that meets environmental protection requirements and can be quickly demoulded by adjusting the polyether component and modifying the isocyanate and using water as a foaming agent. However, the patent does not solve the problems of pinholes and color difference on the foam surface. Patent CN102140163A obtains physical properties similar to physical foaming through water foaming by rationally matching small molecule diols and modifying a variety of isocyanates, with a smooth surface and clear skin. However, the patent also does not solve the problem that the skin is not dense enough and the wear resistance is difficult to meet the standards. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art, provide a spray-free polyurethane self-skinning material and a preparation method thereof, starting from material A, using a large amount of grafted polyether polyol to improve the openness of the foam to eliminate the pinholes on the foam surface, using a specific amount of color paste to avoid surface color difference, and adding an anti-aging agent to meet the light resistance and aging requirements, starting from material B, introducing an appropriate amount of polymerized and modified isocyanate, and using a physical foaming agent, adding low surface energy particles and avoiding the use of a starting catalyst to improve the wear resistance of the foam surface, and finally obtaining a polyurethane self-skinning foam material that can meet the requirements of wear resistance, yellowing and other conventional performance requirements and production process requirements. The problem of the existing polyurethane self-skinning foam requiring spray painting, as well as the appearance, light resistance and wear resistance of the polyurethane self-skinning foam material after not spraying paint are solved.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] A spray-free polyurethane integral skin foam material, comprising the following components, measured in parts by mass:

[0009] A material includes:

[0010]

[0011] Material B comprises diphenylmethane diisocyanate, polymerized diphenylmethane diisocyanate and urethane-modified diphenylmethane diisocyanate.

[0012] In the material A of the present invention, the polyether polyol with a functionality of 3 has a number average molecular weight of 4000-6000, a hydroxyl value of 10-50 mgKOH / g, and polymerization units of propylene oxide and ethylene oxide, and the mass proportion of ethylene oxide is 5%-30%, based on the total mass of propylene oxide and ethylene oxide. Suitable examples include but are not limited to F3135 and F3128 of Wanhua Chemical.

[0013] The grafted polyether polyol of the present invention has a hydroxyl value of 18-32 mgKOH / g, preferably a hydroxyl value of 20-24 mgKOH / g; wherein the solid content of styrene and acrylonitrile is 30-50%, preferably a solid content of 35-45%; the content of the grafted polyether polyol in the A material is greater than 30%, preferably 40-50%, based on the total weight of the A material. Suitable examples include but are not limited to POP2140 and POP3630 of Wanhua Chemical.

[0014] The alcohol chain extender of the present invention is one or more of ethylene glycol, propylene glycol, 1,4-butanediol, 1,3-butanediol, 1,2-butanediol, 1,2-pentanediol, hexanediol, diethylene glycol, triethylene glycol, dipropylene glycol, diethylene glycol or neopentyl glycol.

[0015] The catalyst of the present invention does not contain a strong starting catalyst, such as bis(dimethylaminoethyl) ether (A1), triethylenediamine (A33), pentamethyldiethylenetriamine, trimethylhydroxyethylethylenediamine, N,N,N'-trimethyl-N'-hydroxyethylbisaminoethyl ether (ZF10), and 2,2-bismorpholinyldiethyl ether, and no one or more of them are added.

[0016] The catalyst of the present invention comprises one or more of (1) an organic metal catalyst and (2) a gel and / or equilibrium amine catalyst.

[0017] Preferably, the organometallic catalyst includes one or more of dibutyltin dilaurate, dioctyltin dilaurate, stannous octoate, dibutyltin diacetate, dibutyltin mercaptan, dioctyltin mercaptan, dioctyltin dithioacetate, dimethyltin dithioacetate, zinc carboxylate, and bismuth carboxylate.

[0018] Preferably, the gel and / or balanced amine catalyst includes at least one of dimethylcyclohexylamine, N-methyldicyclohexylamine, pentamethyldipropylenetriamine, dimethylethanolamine, dimethylaminoethoxyethanol, trimethylhydroxyethylpropylenediamine, N,N-bis(dimethylaminopropyl)isopropanolamine, bis(dimethylamino)-2-propanol, dimethylaminopropylamine diisopropanol, N-ethylmorpholine, 1,2-dimethylimidazole, diazabicyclo, 1,4-dimethylpiperazine, tri(dimethylaminopropyl)amine, triethylamine, and tetramethyliminodipropylamine.

[0019] In the material A of the present invention, the anti-aging aid comprises one or more of a light stabilizer and an antioxidant.

[0020] Preferably, the light stabilizer comprises a hindered amine light stabilizer, suitable examples of which include but are not limited to one or more of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate, bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, and 1-(methyl)-8-(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate.

[0021] Preferably, the light stabilizer may also contain one or more benzotriazole ultraviolet absorbers, suitable examples of which include, but are not limited to, ethyl 4-[[(methylphenylamino)methylene]amino]benzoate, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2H-benzotriazol-2-yl)-4,6-di-tert-amylphenol, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-benzotriazole, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3-dodecyl-5-methyl)-benzotriazole, and one or more of 2,4-bis(2',4'-dimethylphenyl)-6-(2'-hydroxy-4'-octyloxy)-1,3,5-triazine.

[0022] Preferably, the antioxidant includes but is not limited to one or more of triethylene glycol bis-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate], 2,6-di-tert-butyl-4-methylphenol, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], thiodiethylene bis[3-(3,5-di-tert-butyl-4-hydroxybenzene) propionate], 3,5-di-tert-butyl-4-hydroxyphenyl propionate octadecyl alcohol ester, N,N-bis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl] hexanediamine, and 3,5-di-tert-butyl-4-hydroxybenzene propionate isooctyl ester.

[0023] Preferably, the content of 4,4'-diphenylmethane diisocyanate in the diphenylmethane diisocyanate exceeds 99%, the solid is white to light yellow-green crystals at room temperature, and it is a transparent liquid after melting, such as WANNATE MDI-100 of Wanhua Chemical.

[0024] The polymeric diphenylmethane diisocyanate is polymeric MDI, which is a mixture of polymethylene polyphenyl diisocyanates with different functionalities, such as WANNATE PM200 of Wanhua Chemical.

[0025] The carbamate-modified diphenylmethane diisocyanate is generally prepared by reacting polyether polyol or polyester polyol with MDI to generate carbamate-modified MDI with a terminal -NCO group, such as WANNATE 8617, WANNATE 8618, and WANNATE 8605 of Wanhua Chemical.

[0026] The content of urethane-modified diphenylmethane diisocyanate in the B material is 40-60%, the content of diphenylmethane diisocyanate is 20-40%, and the content of polymerized diphenylmethane diisocyanate is 15-30%, based on the total weight of the B material.

[0027] The mass fraction of isocyanate group (NCO) of the material B of the present invention is 20-30%, preferably 24-28%.

[0028] In the material B of the present invention, appropriate diphenylmethane diisocyanate can provide a good opening effect of the foam, reduce or avoid the occurrence of pinholes, and meet the appearance requirements. At the same time, the urethane-modified diphenylmethane diisocyanate ensures the toughness required by the foam, and the polymerized diphenylmethane diisocyanate provides a sufficient degree of crosslinking to ensure wear resistance.

[0029] The color paste of the present invention is a color paste of black or other required colors applicable to common commercially available polyurethane.

[0030] The physical blowing agent of the present invention is one or more of hydrochlorofluorocarbon compounds, hydrofluorocarbon compounds, and alkanes, and is preferably one or more of 1,1-dichloro-1-fluoroethane, cyclopentane, pentane, 1,1,1,3,3-pentafluoropropane, 1,1,1,3,3-pentafluorobutane, 1,1,1,2-tetrafluoroethane, and 1-chloro, 3,3,3-trifluoropropylene.

[0031] The low surface energy particles of the present invention are particles with a surface energy of less than 25 mN / m, a size of 1-500 microns and uniform dispersion, preferably polytetrafluoroethylene particles. After adding the low surface energy particles, the particles are evenly distributed on the foam surface, the overall surface energy of the foam surface is reduced, the touch smoothness of the surface is improved, and the wear resistance is significantly improved.

[0032] A method for preparing a spray-free self-skinning foam product comprises the following steps: adopting a closed mold infusion process, spraying a mold release agent on the mold, mixing materials A and B in a mass ratio of A:B=100:30-60, preferably 100:40-50, by a high-pressure foaming machine, pouring into a mold, curing for 90-120s, and then opening the mold to obtain a spray-free product. The material temperature is maintained at 20-30°C, and the mold temperature is maintained at 50°C-60°C.

[0033] Compared with the prior art, the present invention has the following beneficial effects: the present invention provides a method of increasing the amount of grafted polyether, adding low surface energy particles, avoiding the use of a strong starting catalyst, and adjusting the A material component by auxiliary addition of an anti-aging additive, and using a physical foaming agent for foaming, to prepare a high-performance polyurethane self-skinning foam material that does not require spraying mold paint, the appearance reaches the same level as the spray paint foam, there is no color difference, no pinholes, the gloss and touch are basically the same as the spray paint foam, the yellowing resistance and friction resistance meet the requirements, and other common self-skinning foam performance requirements can be met. It solves the environmental pollution, cost increase and employee health problems caused by the need to spray mold paint on the existing polyurethane self-skinning foam material, reduces production links and further improves production efficiency. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.

[0035] If no specific conditions are specified in the examples and comparative examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.

[0036] The raw materials used in the embodiments and comparative examples are as follows:

[0037] A material components:

[0038] Polyether polyol 1, functionality 3, glycerol initiator, hydroxyl value 35 mgKOH / g, polymerization of propylene oxide and ethylene oxide, ethylene oxide content 15%, based on the total mass of propylene oxide and ethylene oxide;

[0039] Polyether polyol 2, functionality 3, glycerol-initiated, hydroxyl value 28 mgKOH / g, polymerization of propylene oxide and ethylene oxide, ethylene oxide content 15%, based on the total mass of propylene oxide and ethylene oxide;

[0040] Grafted polyether polyol 1, functionality 3, glycerol initiator, hydroxyl value 26 mgKOH / g, polymerization of propylene oxide and ethylene oxide, viscosity 5000-5800 mPa·s, solid content of acrylonitrile and styrene 40%;

[0041] Grafted polyether polyol 2, functionality 3, glycerol initiator, hydroxyl value 24 mgKOH / g, polymerization of propylene oxide and ethylene oxide, viscosity 2900-3200 mPa·s, solid content of acrylonitrile and styrene 30%;

[0042] Alcohol chain extender: ethylene glycol;

[0043] Catalyst: triethylenediamine, dimethylaminopropylamine diisopropyl alcohol, dioctyltin mercaptan, dibutyltin mercaptan;

[0044] Anti-aging additives: 2-(2'-hydroxy-3-dodecyl-5-methyl)-benzotriazole, bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, 2-ethylhexyl 3,5-di-tert-butyl-4-hydroxyphenylpropionate;

[0045] Physical foaming agent: dichlorofluoroethane, 1-chloro, 3,3,3-trifluoropropylene;

[0046] Low surface energy particles: polytetrafluoroethylene particles, average diameter 200 μm, DAIKIN, Japan;

[0047] Color paste: black paste;

[0048] B material components:

[0049] Diphenylmethane diisocyanate: WANNATE MDI-100F, NCO content 33.6wt%, Wanhua Chemical;

[0050] Polymeric diphenylmethane diisocyanate: WANNATE PM200, NCO content 31.0wt%, Wanhua Chemical;

[0051] Urethane modified isocyanate: WANNATE 8617, NCO content 23wt%, Wanhua Chemical.

[0052] The polyurethane material for spray-free coating was prepared according to the components shown in Table 1, Examples 1-4 and Comparative Examples 1-5.

[0053] Table 1 Raw materials and dosage

[0054]

[0055] Example 1

[0056] Preparation of material A: Add the measured materials of material A shown in Table 1 into a reaction kettle, stir at room temperature for 1 hour, and then discharge the materials to obtain component A;

[0057] Preparation of material B:

[0058] Put the measured material B shown in Table 1 into the reactor, stir at room temperature for 1 hour, and then discharge the material to obtain component B.

[0059] Preparation of spray-free self-skinning foam products:

[0060] The closed mold infusion process is adopted. After the mold is sprayed with a release agent, materials A and B are mixed evenly according to the mass ratio in Table 1 by a high-pressure foaming machine, injected into the mold, and matured for 90 seconds before the mold is opened to obtain a spray-free self-skinning foam product. The material temperature is maintained at 30°C and the mold temperature is maintained at 60°C.

[0061] Example 2

[0062] The material temperature was maintained at 25° C., and the mold temperature was maintained at 55° C. The rest was the same as in Example 1.

[0063] Example 3

[0064] The material temperature was maintained at 25° C., and the mold temperature was maintained at 50° C. The rest was the same as in Example 1.

[0065] Example 4

[0066] The material temperature was maintained at 25° C., and the mold temperature was maintained at 55° C. The rest was the same as in Example 1.

[0067] Comparative Example 1

[0068] The material temperature was maintained at 30° C., and the mold temperature was maintained at 60° C. The rest was the same as in Example 1.

[0069] Comparative Example 2

[0070] The material temperature was maintained at 25° C., and the mold temperature was maintained at 55° C. The rest was the same as in Example 1.

[0071] Comparative Example 3

[0072] The material temperature was maintained at 25° C., and the mold temperature was maintained at 55° C. The rest was the same as in Example 1.

[0073] Comparative Example 4

[0074] The material temperature was maintained at 30° C., and the mold temperature was maintained at 60° C. The rest was the same as in Example 1.

[0075] Comparative Example 5

[0076] The material temperature was maintained at 30° C., and the mold temperature was maintained at 60° C. The rest was the same as in Example 1.

[0077] Performance test: The spray-free products described in Examples 1-4 and Comparative Examples 1-4, including the spray-free products, were subjected to the following tests:

[0078] Appearance

[0079] Density ISO 845

[0080] Hardness(Shore A)ISO 868

[0081] Light aging resistance HONDA DWG NO 7850Z: aging time 400 hours, back panel temperature 83℃

[0082] Wear-resistant HONDA DWG NO 7850Z: load 1.3Kg, contact double-sided 100mm*45mm cotton cloth, speed 50times / min, dry friction 6000 times and then wet friction with artificial sweat 6000 times to complete one cycle test.

[0083] Smell PV3900

[0084] VOC VDA275

[0085] The test results are summarized in Table 2.

[0086] Table 2 Test results

[0087]

[0088]

[0089] ND* means not detected.

[0090] By comparing the test results of the embodiments and the comparative examples, it is found that the high-performance spray-free material of the present invention has a good appearance without pinholes and color difference without using in-mold paint, meets the requirements of wear resistance and yellowing, and meets other requirements of conventional foam products, and can also be quickly demolded within 90 seconds.

[0091] By comparing Example 1 with Comparative Example 1, it can be found that the polyurethane material without selecting the content of the grafted polyether polyol described in the present invention cannot simultaneously meet the requirements of surface pinhole-free and color difference. By comparing Example 2 with Comparative Example 2, it can be found that the polyurethane material without selecting the polytetrafluoroethylene particles described in the present invention cannot simultaneously meet the requirements of wear resistance. When the color paste content is lower than the range described in the present invention (Example 3 and Comparative Example 3), the color difference distribution difference is large, and the surface color difference and light resistance performance are unqualified by naked eye observation. By comparing Example 4 with Comparative Example 4, it can be found that the polyurethane material without selecting the anti-aging additive described in the present invention cannot meet the requirements of yellowing and light resistance. By comparing Example 1 with Comparative Example 5, it can be found that the use of a strong starting catalyst will lead to a significant decrease in wear resistance, which may cause the foam to fail to meet the wear resistance requirements.

[0092] In summary, the preparation method of the embodiment of the present invention, by using a large amount of grafted polyether, supplemented with anti-aging additives, color paste, low surface energy particles, etc., and adjusting the components of material B, produces a polyurethane material that can be sprayed without in-mold paint and fully meets the conventional performance requirements and production process of self-skinning foam, has good appearance, excellent wear resistance and light resistance. It solves the problems of environmental pollution caused by spraying in-mold paint in the production process of self-skinning foam, reduced production effect and high scrap rate.

Claims

1. A spray-free polyurethane integral skin foam material, comprising the following components, in parts by mass: A material includes: Material B comprises diphenylmethane diisocyanate, polymerized diphenylmethane diisocyanate and urethane-modified diphenylmethane diisocyanate.

2. The spray-free polyurethane integral skin foam material according to claim 1, characterized in that: The grafted polyether has a hydroxyl value of 18-32 mgKOH / g, preferably 20-24 mgKOH / g; the solid content of styrene and acrylonitrile is 30-50%, preferably 35-45%; the grafted polyether polyol content in the A material is greater than 30%, preferably 40-50%, based on the total weight of the A material.

3. The spray-free polyurethane integral skin foam material according to claim 1 or 2, characterized in that: The polyether polyol with a functionality of 3 has a number average molecular weight of 4000-6000, a hydroxyl value of 10-50 mgKOH / g, and polymerization units of propylene oxide and ethylene oxide, wherein the mass proportion of ethylene oxide is 5%-30% based on the total mass of propylene oxide and ethylene oxide.

4. The spray-free polyurethane integral skin foam material according to any one of claims 1 to 3, characterized in that: The catalyst does not contain a strong starting catalyst, and the strong starting catalyst includes bis(dimethylaminoethyl) ether, triethylenediamine, pentamethyldiethylenetriamine, trimethylhydroxyethylethylenediamine, N,N,N'-trimethyl-N'-hydroxyethylbisaminoethyl ether, and 2,2-bismorpholinyldiethyl ether.

5. The spray-free polyurethane integral skin foam material according to any one of claims 1 to 4, characterized in that: The alcohol chain extender is one or more of ethylene glycol, propylene glycol, 1,4-butanediol, 1,3-butanediol, 1,2-butanediol, 1,2-pentanediol, hexanediol, diethylene glycol, triethylene glycol, dipropylene glycol, diethylene glycol, and neopentyl glycol.

6. The spray-free polyurethane integral skin foam material according to any one of claims 1 to 5, characterized in that: The physical blowing agent is one or more of hydrochlorofluorocarbon compounds, hydrofluorocarbon compounds and alkanes, preferably one or more of 1,1-dichloro-1-fluoroethane, cyclopentane, pentane, 1,1,1,3,3-pentafluoropropane, 1,1,1,3,3-pentafluorobutane, 1,1,1,2-tetrafluoroethane, and 1-chloro, 3,3,3-trifluoropropylene.

7. The spray-free polyurethane integral skin foam material according to any one of claims 1 to 6, characterized in that: The low surface energy particles are particles with a surface energy of less than 25 mN / m, a size of 1-500 microns and uniform dispersion, preferably polytetrafluoroethylene particles.

8. The spray-free polyurethane integral skin foam material according to any one of claims 1 to 7, characterized in that: The content of urethane-modified diphenylmethane diisocyanate in the B material is 40-60%, the content of diphenylmethane diisocyanate is 20-40%, and the content of polymerized diphenylmethane diisocyanate is 15-30%, based on the total weight of the B material.

9. The spray-free polyurethane integral skin foam material according to any one of claims 1 to 8, characterized in that: The mass fraction of isocyanate groups in the B material is 20-30%, preferably 24-28%.

10. A method for preparing the spray-free polyurethane self-skinning foam material according to any one of claims 1 to 9, comprising the following steps: using a closed mold infusion process, spraying a mold release agent on the mold, mixing materials A and B in a mass ratio of A:B=100:30-60, preferably 100:40-50, by a high-pressure foaming machine, pouring into the mold, ripening for 90-120s, and then opening the mold to obtain a spray-free self-skinning foam product, wherein: The material temperature is maintained at 20-30℃ and the mold temperature is maintained at 50℃-60℃.

Citation Information

Patent Citations

  • Water foaming self-skin polyurethane composition as well as preparation method and application thereof

    CN101597370B

  • Modified MDI (methane diisocyanate) for cold curing water-blown self-skinning polyurethane foam and preparation method thereof

    CN102140163A

  • Solvent-free polyurethane elastomeric coating with self-lubricating effect

    CN102153944A

  • Self-skinning polyurethane foam plastic and preparation method thereof

    CN103319685A

  • Self-skinning compound material for heat-resistant polyurethane foaming tyre and preparation method thereof

    CN105001394A